What is ecological relevance of ecotoxicology? - Sosak-Świderska , Bożena (Studia Ecologiae et Bioethicae, 2004)
Ecotoxicology is concerned with the toxic effects of chemical and physical agents on living organisms, especially on populations and communities within defined ecosystems; it includes the transfer pathways of those agents and their interactions with the environment. Rene Truhaut, a French toxicologist coined the term ecotoxicology - a new branch of toxicology which defined as the study of the adverse effects of xenobiotics (foreign substances). Both toxicology and ecology are well established. Ecological studies do not typically deal with the organism itself but stress the relation of organisms to their environments. On the contrary toxicological effects occur at many scales: at the cellular or tissue level and enzymes are induced. The most difficult question it seems in ecotoxicology is the choice of the endpoint. Environmentally appealing endpoints such as NOEC (no observable effects concentrations) are difficult to justify Ecotoxicology implies the interfacing of the fields of ecology and environmental toxicology at the population level, there are mortality and selection; at the community level, there is the replacement of species. Most ecotoxicological research to present has used previously existing methods that were expanded into this new field of research, rather than developing new or integrated practices. Research into the transport and chemical transformation of substances has become the field of environmental chemistry, which makes use of analytical techniques (for example QSAR). Ecotoxicology or environmental toxicology and ecology have distinct research programs that identify different problems and that take different things for granted. In addition are there the differences in tools, methods, theories, and concepts, scientists in each of the two disciplines view them as two different fields. Ecotoxicology is a multidisciplinary science and still has not been able to establish itself.